2019
DOI: 10.1155/2019/1545680
|View full text |Cite
|
Sign up to set email alerts
|

Hub Genes and Key Pathway Identification in Colorectal Cancer Based on Bioinformatic Analysis

Abstract: Colorectal cancer (CRC) is one of the most common malignant tumors. The aim of the present study was to identify key genes and pathways to improve the understanding of the mechanism of CRC. GSE87211, including 203 CRC samples and 160 control samples, was screened to identify differentially expressed genes (DEGs). In total, 853 DEGs were obtained, including 363 upregulated genes and 490 downregulated genes. Gene Ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) analysis of DEGs were performed to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 31 publications
0
16
0
Order By: Relevance
“…Multiple studies have indicated that CXC chemokines play vital roles in the development and progression of CRC [ 4 , 9 ]. For instance, CXCL1 has been reported to be associated with CRC progression and metastasis by inducing glycolysis [ 10 ]. Additionally, recent studies have indicated that CXCL8 promotes angiogenesis and cell migration in CRC [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Multiple studies have indicated that CXC chemokines play vital roles in the development and progression of CRC [ 4 , 9 ]. For instance, CXCL1 has been reported to be associated with CRC progression and metastasis by inducing glycolysis [ 10 ]. Additionally, recent studies have indicated that CXCL8 promotes angiogenesis and cell migration in CRC [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Cancer stem cells (CSCs) are involved in the occurrence and recurrence of CRC and have been identified [ 50 ]. Estrogen signaling pathway may be involved in the occurrence of CRC, but the specific mechanism is not yet clear [ 51 ]. These two pathways may be involved in the progression from PRC to LRRC.…”
Section: Discussionmentioning
confidence: 99%
“…The STRING database (http://string-db.org/) is an online tool for high-throughput functional analysis of genes. In this study, the potential associations between the 12 core genes and PLK1 were assessed through the GO annotation analysis and KEGG pathway enrichment analysis [26] [27]. P-values < 0.05 were considered as statistically significance.…”
Section: Go and Kegg Analysismentioning
confidence: 99%